Sistem Pengukuran Detak Jantung Berbasis Visual Menggunakan Plane Orthogonal to Skin dan Peak - Nasrudien, Fahmi; Yulian, Dhany Eka; Lubabsyah, Ahmad Naufal; Firmansyah, Riza Agung; Pambudi, Wahyu Setyo (Forum Kerjasama Pendidikan Tinggi, 2022)
Measurement of vital signs is a procedure that is usually done when health workers carry out screening. The vital signs in question include body temperature, heart rate, blood pressure, oxygen saturation and others. The equipment used to measure these vital signs should generally be touched to the subject (by contact). However, due to the COVID-19 pandemic, contact measurements need to be avoided. So it is necessary to make a non-contact measuring system for vital signs. In this study, the only vital signs measured were heart rate. In this study it is proposed to make a non-contact heart rate meter with a plane orthogonal to skin (POS) that uses a peak detection algorithm to determine the heart rate value. In general, the POS method using the fast Fourier transform (FFT) requires longer data which makes the process take longer. So in this study, a peak detection algorithm will be used to calculate the heart rate value that has been extracted using POS which has a faster process. Based on the testing of the POS-FFT method and the POS-peak detection method, it was found that POS-peak detection gave stable results at all data lengths. The smallest mean absolute error generated is with a data length of 128 which is 5.19 bpm